Variasi Latihan Shooting Drill untuk Meningkatkan Keterampilan Shooting Pemain Bola Basket pada Tingkat Sekolah Menengah Atas di Kota Malang - A'yun, Rizquna Qurrota; Supriyadi, Supriyadi; Sugiarto, Dinta (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2024)
Basketball is a two-team sports model of five players each to score by putting the ball into the opponent's hoop and blocking the opponent from scoring. A player should be proficient in mastering basic techniques, one of which is shooting which is the most commonly used technique because the goal is to put the ball into the opponent's ring through shooting. The focus of this study was to determine the effect of variations in shooting training on shooting skills in extracurricular basketball participants in grade X of high school in Malang. The research design used is pre-experimental design included in One Group Pretest-Posttest Design.The sampling technique in this study is a non-probability sampling technique of purposive sampling type, therefore a sample of 23 participants was obtained. The data analysis used are descriptive analysis techniques, normality tests, homogeneity tests, and hypothesis tests. The results of this research analysis using paired sample t-test analysis with STO basket per minute (shooting test) test showed a significant value (2-tailed) of 0.000 so this study concludes that there is an influence of shooting drill training variations on shooting skills in class X basketball extracurricular participants at the Senior High School level in Malang City.